An isolated, surface-expressed I domain of the integrin αLβ2 is sufficient for strong adhesive function when locked in the open conformation with a disulfide bond - Lu, Chafen (The National Academy of Sciences, 2001)
We introduced disulfide bonds to lock the integrin αLβ2 I domain in predicted open, ligand binding or closed, nonbinding conformations. Transfectants expressing αLβ2 heterodimers containing locked-open but not locked-closed or wild-type I domains constitutively adhered to intercellular adhesion molecule-1 (ICAM-1) substrates. Locking the I domain closed abolished constitutive and activatable adhesion. The isolated locked-open I domain bound as well as the activated αLβ2 heterodimer, and binding was abolished by reduction of the disulfide. Lovastatin, which binds under the conformationally mobile C-terminal α-helix of the I domain, inhibited binding to ICAM-1 by αLβ2 with wild-type, but not locked-open I domains. These data establish the importance of conformational change in the αL I domain for adhesive function and show that this domain is sufficient for full adhesive activity.